Pengaruh Green Human Resource Management terhadap Kinerja Lingkungan yang Dimediasi oleh Komitmen Organisasioanal (Studi Kasus pada PT Bank Boyolali) - Riko Iswantoro; Irmawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the influence of green human resource management on environmental performance mediated by organizational commitment. This research is included in quantitative research. The population of this research is employees of PT Bank Boyolali. The sample collected in this research was 73 respondents. The data used is primary data where data is obtained from respondents' answers through the questionnaire that has been given. The results of this research indicate that Green Human Resource Management does not have a significant influence on Environmental Performance. Green Human Resource Management has a positive and significant influence on Organizational Commitment. Organizational Commitment has a positive and significant influence on Environmental Performance. Organizational Commitment can mediate the relationship between Green Human Resource Management and Environmental Performance.